THE EFFECT OF TEMPERATURE ON THE SYNTHESIS OF CALCIUM CYANAMIDE AND THE COMPOSITION OF THE EXHAUST GASES - O. H. Panzhiev; A. Kh. Panzhiev; M. B. Norkulov (International Engineering Journal For Research & Development, 2020)
For the first time thermodynamic calculations on rather new physical and chemical constants specify temperature of the beginning of thermal decomposition of ammonia, and also probability of collateral chemical reactions between ammonia and carbon dioxide. Influence on synthesis cyanamid calcium of the basic technological parameters is investigated. The structure of departing gases from a reactor of synthesis cyanamid calcium depending on temperature is studied. Kinetic researches of process of synthesis cyanamid calcium certain orders of chemical reaction on ammonia and carbon dioxide and is proved, that a limiting stage of process of synthesis cyanamid calcium is diffusion of initial gas components through a layer of a product.